PENGARUH LABA KOMERSIAL, PENDAPATAN PAJAK TANGGUHAN TERHADAP BEBAN PAJAK DI BURSA EFEK INDONESIA - Enggun Gunawan (JURNAL LENTERA AKUNTANSI, 2019)
The purpose of this study is to determine the effect of commercial net income and deferred tax income to current tax expense, simultaneously (together) and partial (separate). The sampling method used is purposive sampling to obtain 46 financial statement data of manufacturing companies whose shares are listed in Indonesia Stock Exchange (BEI), 46 data of this financial statements consist of 23 sample companies with year of research 2014 and 36 other sample company with year of research 2015 The data were analyzed by regression model of panel data using the help of computer statistic application program Eviews 7.0. The results of this study are: t test result states that hypothesis 1 is accepted while hypothesis 2 is rejected, ie the net commercial net profit partially significant to current tax burden while the deferred tax income does not significantly affect the current tax burden. In addition, hypothesis 3 is accepted that the result of F test states that commercial earning and deferred tax income significantly influence the current tax burden which is tested simultaneously. Keywords: commercial net income, deferred tax income, current tax expense